Partial discharge measurements in the three-layer dielectrics with a barrier; Conference Record of the 2004 IEEE International Symposium on Electrical Insulation (Indiana Convention Center, Indianapolis, IN, 19 - 22 September 2004 ) - Lebedev S. M.; Gefle O. S.; Pokholkov Y. P. Yuri Petrovich; Gockenbach E.; Borsi H.; Wasserberg V.; Abedi N.; Szczechowski J. (2004, 2004)
It is a well-known fact that the breakdown voltage of dielectrics in a divergent field may be increased by using an additional insulating layer (A barrier) placed at the optimal position between the electrodes. In our previous works we reported that this effect is observed not only in the divergent electric field but also in moderately nonuniform and quasiuniform electric fields. This work is devoted to the investigation of the barrier effect in solid dielectrics in a quasiuniform electric field, i.e. the study of relationship between partial discharge activity and the barrier position in the insulating gap. It is established that PD-parameters depend on the barrier position in the gap. In particular, the ignition voltage of PD with magnitude of 10 pC is increased by 20-50% at the optimal barrier position compared to that for other barrier positionsSummary: It is a well-known fact that the breakdown voltage of dielectrics in a divergent field may be increased by using an additional insulating layer (A barrier) placed at the optimal position between the electrodes. In our previous works we reported that .....Summary: In this paper composite solid dielectrics were studied by using the dielectric spectroscopy method in frequency domain. Dielectric relaxation spectra of composite materials on the basis of natural and synthetic rubbers and LDPE filled with a ferroele.....